PENGARUH LATIHAN MODIFIKASI DAN RESISTANCE BAND TERHADAP PENINGKATAN REAKSI PADA ATLET BULU TANGKIS PB. MANDIRI HUSADA PALOPO - Rahmaniar; A. Heri Riswanto; Nasriandi; Ahmad Syarif Burhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of modified training and Resistance Band exercises on improving reaction time in badminton athletes of PB Mandiri Husada Palopo. This research employed an experimental method with a two-group pretest- posttest design. The sample consisted of 20 athletes divided into two groups: Group A performed modified training, while Group B performed Resistance Band training, with a frequency of 16 sessions. The instrument used was a reaction speed test with a metal ruler held above the athlete’s hand. The data analysis results showed that both types of training had a significant effect on improving reaction time. Based on the paired sample t-test, the significance value obtained was (p < 0.05) in both groups. Furthermore, the independent sample t-test results indicated no significant difference between Group A and Group B (p = 0.0685). Therefore, it can be concluded that modified training and Resistance Band training do not have significant differences in improving reaction time.